Distribution of load among the balls in the radial bearings. Part 2. Solution for summer-variational methods to asses. - Кузьменко, А.Г.; Сабадаш, Б.М. (Problems of Tribology, 2015)
This part describes how to apply the new solution of the problem of variational-experimental method, demonstrated the efficacy of the use of the method. Part 1 cm. [2].